Serum uromodulin is a predictive biomarker for cardiovascular events and overall mortality in coronary patients. (15th March 2017) - Leiherer, Andreas; Muendlein, Axel; Saely, Christoph H.; Ebner, Janine; Brandtner, Eva M.; Fraunberger, Peter; Drexel, Heinz
Abstract: Background: Uromodulin is a protein produced exclusively by the kidneys and present in urine and blood. In contrast to weak and in part contradictory study data on uromodulin in urine samples, the analysis of serum samples recently proved uromodulin's value as superior biomarker for ongoing kidney disease. Whether serum uromodulin is associated with cardiovascular event risk and whether it has predictive power for overall mortality is still unknown and has been evaluated in the present study. Methods: We measured uromodulin in a series of 529 patients without acute coronary syndrome undergoing coronary angiography for the evaluation of established or suspected stable coronary artery disease (CAD) and prospectively recorded mortality as well as cardiovascular events in our patients during a follow-up of up to 8 years. Results: We recorded 95 deaths and 145 cardiovascular events over 8 years. Serum uromodulin proved protective for overall mortality (HR = 0.56 [95%CI 0.43–0.72]; p < 0.001), even after full adjustment including eGFR, current smoking, diabetes, and CAD status (adj. HR = 0.57 [95%CI 0.37–0.89]; p = 0.014). Patients in the lowest tertile of serum uromodulin had a significantly higher cardiovascular event risk compared to patients in the medium and highest tertile (HR = of 1.45 (95%CI 1.04–2.02, p = 0.027). The ratio between creatinine and uromodulin was significantly associated with kidney function (r = − 0.322; p < 0.001) and significantly predicted the incidence of cardiovascular events (HR of 1.26 [95%CI 1.12–1.41], p < 0.001) and major cardiovascular events (HR of 1.37 [95%CI 1.21–1.56], p < 0.001). Conclusion: We conclude that serum uromodulin is a valuable biomarker to predict overall mortality and cardiovascular events.